Analisis Beban Kerja Ditinjau Dari Faktor Usia Dengan Pendekatan Recommended Weiht Limit ( Studi Kasus Mahasiswa Unpatti Poka) - Aminah Soleman (ARIKA, 2011)
Recommended Weight Limit is a condition in which nearly all workers can do the job appointment to normal within a certain time period without incurring the risk of spinal injuries caused by lifting. The purpose of this study was to assess and classify the physical workload based workload increased pulse rate on unskilled labor while doing removal work load, analyze the optimal use of the load based on the approach to the Recommended Weight Limit, and determine the influence of heavy workloads in accordance with the criteria Lifting index. Calculations based on the physiological approach performed in a subjective order to obtain the lifting of activities for the whole treatment in the category of mild working conditions, and based on the Recommended Weight lifting load limit is obtained optimal for untrained workers with 19-24 years of age based on multiplier factor of the distance measurement position of the hand holding horizontal load (H), vertical distance of the hand holding the position of the load on the floor (V), the distance moved by the load vertically between the place of origin to destination (D), the angle of rotation symmetry is formed between the hands and feet (a), Frequency multiplier (F) with the duration of the appointment of> 1 hour can handle load of 22 kg. Based on Lifting Index for unskilled labor is obtained that the work load of 15 kg, 20 kg and was not identified at risk of injury to the spine because the value of LI> 1, but for the work load of 25 kg identified the risk of spinal injury to workers are not trained as LI values <1.